Proses Penentuan Ibukota Kabupaten Kediri pada Tahun 2021–2023 - Jenny Agustina Rahmadi; Wisnu W (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Determining the seat of local government is a strategic step to optimize governance, improve public services, and affirm the identity of Kediri Regency. Using the historical method—heuristics, criticism, interpretation, and historiography—this study examines the procedural stages, political-governmental dynamics, and historical-cultural considerations behind the naming of Kediri Regency's new capital between 2021 and 2023. Primary data were drawn from official archives, regional regulations, and an interview with a local cultural figure, complemented by secondary literature. The findings show that the government's renewed initiative in 2021, following an unrealized attempt in 2013, involved academic collaboration with Universitas Negeri Surabaya together with historians, cultural figures, and community leaders to trace the region's toponymic history through the Pamwatan Inscription, the Calon Arang manuscript, and Panji literature. Two candidate names, Daha and Pamenang, emerged from this process; a public survey recorded 59.2% support for Pamenang, which the Regional House of Representatives (DPRD) formally approved through Decree Number 2 of 2023. The designation was subsequently followed by Regional Regulation Number 6 of 2023 on Spatial Planning, which repositioned Pamenang within a broader development strategy supported by the Kertosono–Kediri toll road and Dhoho International Airport.